Development of Biofertiliser Based on Agricultural Waste for Sustainable Agriculture - Marningot Situmorang; Boy Angga (CV. HEI PUBLISHING INDONESIA, 2024)
Based on data from the Central Statistics Agency (BPS), the use of chemical fertilisers in Indonesia has increased by 50% in the last two decades, contributing to the decline of soil fertility and groundwater pollution (Rosadi, 2023). Research by the Indonesian Institute of Sciences (LIPI) found that the use of biofertilisers from agricultural waste can reduce the need for chemical fertilisers by up to 40%, while improving soil fertility in a sustainable manner. This research will focus on the development of agricultural waste-based biofertiliser formulations, with trials of their application in various crop types and land conditions in Indonesia. This research uses an experimental method with a quantitative approach, which aims to develop and test the effectiveness of agricultural waste-based biofertilisers. Table 1. The Bima variety (a1) has a larger number of plants than the Mentes variety (a2). Nutrient management also has a major impact on plant growth. Application of one dose of recommended NPK together with 100 kg/ha of pearl NPK (b3) and one dose of recommended NPK together with organic fertiliser and biofertiliser (b4) resulted in the highest plant growth at 8 weeks of age (Table 1). In the experiment, intensive pest control was carried out in the field. As a result, onion caterpillar (Spodoptera exigua hubn) populations per clump were low and fusarium wilt (Fusarium oxysporum hanz) infestation levels were generally low in both variety and nutrient management treatments. There was no evidence that varietal treatments or nutrient management had a significant impact. The application of agricultural waste-based biofertilisers not only improves crop yields, but also supports the sustainability of the agricultural ecosystem by minimising the use of synthetic chemicals and optimising the use of available resources.